The multifunctional pastoral systems in the Mediterranean EU and impact on the workforce - Ragkos A.; Nori M. (Ecosystem services and socio-economic benefits of Mediterranean grasslands, 2016)
Pastoralism constitutes a multifunctional system of animal production; the system is endowed with a range of values, which, nonetheless, are not captured in the prices of products. Indeed, pastoralism protects rural livelihoods – especially in marginal and remote areas which, in the absence of inhabitants, would become abandoned or nurturing illegal activities –, is endowed with important cultural features, produces high-quality dairy products and plays an irreplaceable role in preserving and maintaining ecosystem functioning. An important function of the system lays in the provision of income and employment to communities inhabiting mountainous or remote areas, for whom productive opportunities are limited. The purpose of this study is to present the main functions of pastoralism, alongside with the main pre-conditions for the protection and development of its various forms in the Mediterranean (transhumance, island animal production, grassland-based livestock farming). The study focuses on necessary political, social and regulatory adjustments to formulate a favorable operational environment, which should accommodate its unique multifunctional features and differentiate it from conventional intensive or semi-extensive systems. The discussion is extended to the role of immigrant farm workers in the reproduction of pastoralism.
15. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM International Network for the Research and Development of Pastures and Fodder Crops, 2016/04/12-14, Orestiada (Greece)